Immigrant peers in the class: Responses among natives and the effects on long-run revealed preferences - Helena Holmlund; Erica Lindahl; Sara Roman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
We investigate whether exposure to immigrant peers at school affects natives' future interactions with ethnic minorities. Identification is based on variation in immigrant exposure across cohorts within school catchment areas in Sweden. We document that natives respond to immigrants by changing school and develop an IV strategy that accounts for such endogenous responses. Our results show that minority exposure at the extensive margin increases the probability that natives form inter-ethnic romantic partnerships, which is suggestive of altered preferences for interacting with immigrants. We also find that minority exposure affects women's educational choices and family formation decisions in a family-oriented direction.
Keywords: J12; J15; I2; 330; contact hypothesis; peer effects; intermarriage